2022
DOI: 10.3390/biomedicines10020200
|View full text |Cite
|
Sign up to set email alerts
|

Biologics in Severe Eosinophilic Asthma: Three-Year Follow-Up in a SANI Single Center

Abstract: Introduction: Biologic drugs have dramatically improved severe eosinophilic asthma (SEA) outcomes. Our aim was to evaluate the long-term efficacy of biological therapy in SEA in a real-life setting and to identify the predictors for switching to another biological drug in patients with poor asthma control. The outcomes for efficacy were decreased annual exacerbations (AE) and improved asthma control test (ACT). Methods: In 90 SEA patients being treated with a biological drug, clinical examination, ACT, blood e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…In our cohort, only two patients were in therapy with biological drugs, suggesting that most of them had a mild-to-moderate asthma which was likely to be kept under control with a proper adherence to standard therapies [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort, only two patients were in therapy with biological drugs, suggesting that most of them had a mild-to-moderate asthma which was likely to be kept under control with a proper adherence to standard therapies [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the patients enrolled in our study had, in fact, a proper prescription as per GINA guidelines [ 8 ]; however, only half of them took their prescription regularly. Adherence to medication regimes with ICS in asthma has always been notoriously low, with estimates showing as little as 30% [ 30 ]. Nevertheless, in the first wave of the pandemic, such a percentage increased by 14% therefore varying between 54 and 61% [ 33 ], mainly due to the fear of worse clinical outcomes, as previously stated.…”
Section: Discussionmentioning
confidence: 99%
“…50 Among these patients, the percentage on OCS dropped from 41% to 12% over the course of the study. 50 In total, 43% of non-responders still needed OCS treatment despite shifting to another biologic after 12 months. 50 However, switching treatment resulted in significant improvements in the incidence of AEs, as well as improvements in clinical measures of asthma (asthma control test [ACT] and forced expiratory volume after 1 second).…”
Section: Oral Corticosteroid Stewardshipmentioning
confidence: 94%
“…49 Analysis from the SANI registry similarly indicates that biologics reduce long-term OCS use. 50 In a 3-year follow-up in a SANI singlecentre study, 75% of 90 patients with severe eosinophilic asthma were found to respond to biologic therapy. 50 Among these patients, the percentage on OCS dropped from 41% to 12% over the course of the study.…”
Section: Oral Corticosteroid Stewardshipmentioning
confidence: 99%
See 1 more Smart Citation